Perspectivas acerca das racionalidades constitutivas do arquivo no âmbito da governamentalidade - Tavares, Derek Warwick da Silva (2019)
The study considers the archives as institutions and spaces of consignment and hermeneutics that allow control and access to information, but which, moreover, are located in areas of political interrelationship. In approaching governmentality, it seeks to situate it as a heuristic instrument of practices and techniques of government execution within political rationalities. Concepts are articulated in order to perceive the strategic, technical relations that promote the constitutive rationalities of the archive as an instrument of political power. Thus, the research describes the dynamics of the archival institution from the concept of "governmentality", as developed in the work of Michel Foucault. In order to do so, it undertakes reflections on the contexts that would lead to the over determination of the information phenomenon and the frames of social memory from the constitutive rationalities of the archives. It adopts as a methodological principle the notion of "genealogy" present in Foucault and Nietzsche, which led to the characterization of a bibliographic delineation research, in the restricted use of secondary sources to articulate theoretical, conceptual and analytical elements of the conceptions of "governmentality", rationality and which, in turn, were substantial for the procedural undertaking of research at the descriptive level. It also considers that the archive is a device of political power, through which actions of governmentality are operated in the instances of information control and knowledge, as well as surveillance, capture, registration and use of information in panoptic practices. It is, therefore, a research that presents the archive as a strategic political-administrative tool of the State, through the disciplinary and vigilant use of the behavior of the subjects and the population.